Pengaruh Disiplin Kerja, Budaya Organisasi dan Gaya Kepemimpinan Terhadap Kinerja Karyawan PT. Clipan Finance Indonesia Tbk - Khamsir, Khamsir (KRAKATAU (Indonesian of Multidisciplinary Journals), 2023)
This study aims to research the influence of leadership style, organizational culture, and work discipline partially and simultaneously on employee performance. The data used in this study are primary and secondary data obtained from the field and library data. The sample in this study were 70 employees of PT Clipan Finance Indonesia Tbk. By using simple random sampling method. This type of research is quantitative. The analysis performed is multiple linear regression using SPSS 25. The results of this study indicate that leadership style, organizational culture, and work discipline are partially and simultaneously have a significant effect on the performance of PT Clipan Finance Indonesia Tbk